RISK ASSESSMENT OF THE MALAYSIAN AGRICULTURE, FORESTRY, AND FISHING FATALITIES USING FAULT TREE ANALYSIS (Journal of Energy and Safety Technology (JEST), 2026)
Malaysia’s agriculture, forestry and fishing sector has persistent fatality risks, shaped by mechanisation, remote work settings, and informal employment. This study analysed 103 fatal AgFF accidents investigated by the Malaysian Department of Occupational Safety and Health (DOSH) between 2010 and 2020, using structured extraction from case summaries to derive accident type, activity, employment status, state, exposure set, and source of injury. Descriptive analysis summarised distributions, and associations were tested using chi square with effect size measures. A fault tree model was then constructed to represent plausible causal pathways linking exposure sets and sources of injury to accident types. In descriptive counts, “struck by object” was the most frequent fatal accident type. In the fault tree results, “fall from height” ranked higher because the model estimates scenario contributions along dominant exposure source pathways, rather than reporting raw marginal frequencies only. The findings prioritise prevention efforts around transport related tasks and tractor or trailer scenarios, alongside targeted controls for struck by object events.
Keywords: fatal injury; agriculture; forestry and fishing; fault tree analysis